Factorial Validity and Measurement Invariance of the Slovene Version of the Cultural Intelligence Scale - Boštjančič, Eva; Komidar, Luka; Johnson, Richard B. (Frontiers in Psychology, 2018)
This study examined the factorial validity of the Slovene version of the Cultural Intelligence Scale (CQS) in a representative sample of 1000 Slovenian participants (49% were female). The results of confirmatory factor analysis supported the factorial validity of the Slovene CQS and the existence of a general (second-order) cultural intelligence factor. The four scales and the overall (general) CQS scale showed satisfactory internal consistency. The results of multiple-group confirmatory factor analyses supported the hypotheses of partial measurement invariance across gender, and full measurement invariance across type of settlement (urban vs. rural).